OPTIMAL DOSE AND ADVERSE EFFECTS OF METHOTREXATE USED IN RHEUMATOID ARTHRITIS IN A TERTIARY CARE HOSPITAL OF PAKISTAN: Adverse Effects of Methotrexate - ., Dr. Shazia Zammurrad; ., Abid Farooqi (Pakistan Armed Forces Medical Journal, 2013)
Objective: To find out optimum dosage and frequency of side effects with methotrexate (MTX) used in rheumatoid arthritis (RA).Design: Quasi experimental study.Place and duration of study: Department of Rheumatology, Pakistan Institute of Medical Sciences, Islamabad from November 2011 to April 2012Patients and Methods: Patients of rheumatoid arthritis were treated with methotrexate (MTX). Dosage of MTX ranged from 7.5 to 30 mg per week. In patients who were tolerating MTX and still had an active disease according to DAS 28 index, their dose was increased further. The dose was increased till the disease activity was controlled or they developed side effects. Each case was followed on monthly basis for a total of 6 months. In the end all the data was analyzed.Results: Out of 103 patients, 78 successfully completed the study. Mean age of patients was 42.4 ± 12.7 years and disease duration was 4.9 ± 4.6 years. After 6 months of therapy, it was observed that an average dose of 13.9 ± 4.2 mg per week of methotrexate was well tolerated by the patients. Side effects included: gastrointestinal 38(48.7%), neuropsychiatric 22(28.2%), dermatological 10(12.8%), reproductive 3(3.8%) and respiratory 1(1.3%).Conclusion: An average of 13.9 ± 4.2 mg per week of MTX was found to be the optimum dose which was used and tolerated by most of the patients. Most common adverse effects were gastrointestinal while respiratory were the least common in the study.